2009
DOI: 10.1002/poc.1582
|View full text |Cite
|
Sign up to set email alerts
|

Unsymmetrical dyes derived from 7,8‐dihydrobenzo[c,d]furo[2,3‐f]indole

Abstract: On the basis of the 7,8-dihydrobenzo [c,d]furo [2,3-f]indole nucleus, a number of unsymmetrical carbocyanines as well as styryl dyes have been synthesized and their absorption spectra have been measured. Starting from the deviations of long-wavelength maxima, the value of electron-donor ability D has been estimated for the heterocycle under study and a number of dye end groups have been ranked by their electron-donor properties. Experimental inferences are supported by the quantum chemically calculated bond le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…These studies concluded that the positive charge (zwitterionic structure) in the donor moiety of the merocyanines mainly lies on the nitrogen atom, except for the benzoxazole heterocycle, where the contribution of the O + form is no longer negligible. , This conjugation effect can be observed in the absorption spectrum of dye 1 , which is slightly blue-shifted in comparison with that of the other dyes of this series, in particular, dyes 3 and 4 , similar to other benzoxazole-containing compounds described in the literature . Dyes bearing a benzo­[ c , d ]­indole donor moiety have been found to show the highest effective conjugation length among nitrogen-containing heterocycles, , thus shifting the molecular absorption to the near-infrared region, as seen for dye 8 . On the other hand, dye 9 shows a sharper absorption at shorter wavelengths due to the lack of the dicyanovinyl acceptor group, i.e., the shorter conjugation path provided by the 1,3-indanedione acceptor unit.…”
Section: Resultssupporting
confidence: 72%
“…These studies concluded that the positive charge (zwitterionic structure) in the donor moiety of the merocyanines mainly lies on the nitrogen atom, except for the benzoxazole heterocycle, where the contribution of the O + form is no longer negligible. , This conjugation effect can be observed in the absorption spectrum of dye 1 , which is slightly blue-shifted in comparison with that of the other dyes of this series, in particular, dyes 3 and 4 , similar to other benzoxazole-containing compounds described in the literature . Dyes bearing a benzo­[ c , d ]­indole donor moiety have been found to show the highest effective conjugation length among nitrogen-containing heterocycles, , thus shifting the molecular absorption to the near-infrared region, as seen for dye 8 . On the other hand, dye 9 shows a sharper absorption at shorter wavelengths due to the lack of the dicyanovinyl acceptor group, i.e., the shorter conjugation path provided by the 1,3-indanedione acceptor unit.…”
Section: Resultssupporting
confidence: 72%
“…Various chemical methodologies were applied for increasing the L-parameter, which enable shifting the dyes absorption to the near-IR region, such as benzannelation of heterocycles used as TG [91][92][93], using of non-alternated hydrocarbons [94,95] and their heteroanalogues (2-azaazulene or pseudoazulene, such as indeno[2,1-b]chromene) [96,97] and the introduction of π-donor substituents (OCH 3 , N(CH 3 ) 2 ) to sensitive positions of TG [98,99]. Such spectral response to the TGs chemical modification provides possibility to create the near-IR dye, which could absorb light at ∼1000 nm, with the variation of relatively short polymethine chain (figure 6).…”
Section: Why Cyanine Dyes?mentioning
confidence: 99%